Innovative Hint-Scaffolded KM E-learning Framework To Increase Meaningful Learning And Multi-Dimensional Thinking - Chin, Sylvia; Lee, Chien-Sing (Design and Technology Education: An International Journal, 2014)
Remote and rural communities are often disadvantaged in terms of access to infrastructure, information and opportunities. The authors are concerned with two specific problems crucial to promoting sustainable online learning for the remote community. First, presenting learning content may not be sufficient to help students to improve their learning as they are not competent to make meaning from the information presented. Second, students are often not competent to articulate information from different perspectives or discuss complex issues. The authors’ contributions are in four aspects (i) instructional design of learning activities, especially role playing (ii) design of learning content (iii) design of hint-based teaching-learning strategies to scaffold learning and (iv) design of technology-enhanced collaborative learning. This Knowledge Management (KM) framework has been used for the development of an instructional model incorporating a germane pedagogical setup which coalesces interactive learning and learner-centered factors. The process was illustrated with a case study from SMK Bario, Sarawak (Sekolah Menengah Kebangsaan, local secondary school) with Form 2 students (14-15 years old) to show that the recommended matrix method has been applied to make a successful transition to a blended learning format that combines face-to-face sessions with distance communication. Findings indicated that students were able to filter and consider multiple perspectives, skillfully represent the problem in more ways than one, capable to quickly change focus and goals as the situation required and able to post questions about complicated and complex issues in open class discussions. The authors investigated whether KM processes, e-learning principles and Human Factors Engineering will promote sustainable online learning for the remote community.